Doryphoribius neglectus sp. n. and Parascon nichollsae sp. n., new species of eutardigrades from Australia - Pilato, Giovanni; Lisi, Oscar (Zootaxa, 2004)
Two new species of tardigrades are described from Western Australia: Doryphoribius neglectus sp. n. and Parascon nichollsae sp. n.. The peculiar shape of the stylet furcae distinguishes Doryphoribius neglectus sp. n. from all the known species of the genus. As well, the new species differs from some of them in having a smooth cuticle, or in the number of macroplacoids, or in some characters of the claws. Parascon nichollsae sp. n. is the second species of the genus. It differs from Parascon schusteri Pilato & Binda, 1987 in characters of the bucco-pharyngeal apparatus and in having shorter claws.